Analysis of User Experience Quality of Automobile Spare Parts Sales Information System Using User Experience Questionnaire Method - Muhammad Ridho Pramana Ridho; Faldi Handika Sarumaha; Murdani Murdani (STMIK Methodist Binjai, 2026)
The development of information technology has encouraged business sectors to utilize information systems to support operational activities, including the car spare parts sales process. However, the implementation of an information system should not only be evaluated from its functional aspects, but also from the quality of user experience. This study aims to analyze the quality of user experience in the car spare parts sales information system at CV Sumatra Motor using the User Experience Questionnaire (UEQ) method. The UEQ instrument consists of 26 question items covering six dimensions, namely attractiveness, efficiency, perspicuity, dependability, stimulation, and novelty. Data were collected through questionnaires distributed to system users and then processed by calculating the mean score for each UEQ dimension. The results showed that the overall mean score was 2.09, which is categorized as very good. The stimulation dimension obtained the highest score of 2.19, followed by perspicuity with 2.18 and attractiveness with 2.14. Meanwhile, the novelty dimension obtained the lowest score of 1.92, but it still falls into the good category. These results indicate that the system provides a positive user experience, particularly in terms of ease of use, comfort, and user engagement. Nevertheless, the novelty aspect still needs improvement through feature development, interface refinement, and system innovation to provide a more optimal user experience.